Respuesta :

Answer:

see explanation

Step-by-step explanation:

B

To determine if (2, - 1) is a solution to y = 3x - 2

Substitute x = 2 into the equation and if the result is equal to the y- coordinate of the point then it is a solution.

y = 3(2) - 2 = 6 - 2 = 4 ≠ - 1

Thus (2, - 1) is not a solution to the equation.

D

The point (2, - 1) only lies on the line sloping downwards from left to right.

It is therefore a solution to that equation but not the other.

B)

~ Substitute x = 2 into the equation and if the result is equal to the y- coordinate of the point then it is a solution.

~ y = 3(2) - 2 = 6 - 2 = 4 ≠ - 1

(2, - 1) is not a solution to the equation.

D)

~ The point (2, - 1) only lies on the line sloping downwards from left to right.

~ So it’s is a solution to that equation.

ACCESS MORE